High prevalence of antimicrobial resistance in non-vaccine serotypes of non-invasive/colonization isolates of Streptococcus pneumoniae: A cross-sectional study eight years after the licensure of conjugate vaccine in Japan - Mitsuyo Kawaguchiya; Noriko Urushibara; Meiji Soe Aung; Masahiko Ito; Ayana Takahashi; Satoshi Habadera; Nobumichi Kobayashi (Elsevier, 2020)
Background: Multidrug resistance (MDR) in non-vaccine serotypes (NVTs)-Streptococcus pneumoniae is a global public health concern after the widespread use of pneumococcal conjugate vaccines (PCVs). The present study aimed to analyze the prevalence of serotypes and antimicrobial susceptibilities of non-invasive/colonization isolates of S. pneumoniae eight years after the introduction of PCV in Japan. Methods: A total of 545 non-invasive pneumococcal isolates (460 children, 85 adults) obtained from July 2018 to January 2019 were studied. All isolates were tested for susceptibility to ten antimicrobials and were characterized for serotypes, penicillin binding protein (PBP) genotypes, and macrolide resistance genes. Results: Among children, 95.0% of isolates belonged to non-13-valent pneumococcal conjugate vaccine (PCV13) serotypes (NVTs), with 15A (15.0%) being dominant, followed by 35B (12.2%), 23A (11.1%), 15B (9.8%), and 15C (9.6%). In contrast, serotype 3 (18.8%) was the most prevalent in adults, while 15A, 10A, and 23A were also common. Serotypes covered by PCV13 and 23-valent pneumococcal polysaccharide vaccine (PPSV23) in all the adult isolates were 25.9% and 48.2%, respectively. High resistance rates were observed against erythromycin, tetracycline, and clindamycin (≥62.4% children, ≥58.8% adults). Penicillin-resistant and penicillin-intermediate isolates represented 2.2% and 33.8% of all isolates, respectively. Most isolates of the three dominant NVTs 15A, 35B, and 23A were non-susceptible to penicillin. Overall, multiple drug resistance (MDR) was detected in 69.0% of all isolates, including dominant NVTs 15A, 35B, 23A, 15B, and 15C. Among all the isolates, 81.8% harbored at least one altered PBP genes, and erm(B), mef(A/E) and both these genes were found in 68.2%, 23.3%, and 6.8%, respectively. High prevalence (>90%) of erm(B) was observed in serogroup 15, and serotypes 23A, 33F, and 12F. Conclusion: The present study revealed the high prevalence of NVTs 15 and 23A, and 35B showing MDR, suggesting their spread after introduction of routine PCV immunization.